Self-Measured vs Professionally Measured Waist Circumference - Carranza Leon, Barbara G. (Ann Fam Med, 2016)
PURPOSE: Although waist circumference can provide important metabolic risk information, logistic issues inhibit its routine use in outpatient practice settings. We assessed whether self-measured waist circumference is sufficiently accurate to replace professionally measured waist circumference for identifying high-risk patients. METHODS: Medical outpatients and research participants self-measured their waist circumference at the same visit during which a professionally measured waist circumference was obtained. Participants were provided with standardized pictorial instructions on how to measure their waist circumference, and professionals underwent standard training. RESULTS: Self- and professionally measured waist circumference data were collected for 585 women (mean ± SD age = 40 ± 14 years, mean ± SD body mass index = 27.7 ± 6.0 kg/m(2)) and 165 men (mean ± SD age = 41 ± 14 years, mean ± SD body mass index = 29.3 ± 4.6 kg/m(2)). Although self- and professionally measured waist circumference did not differ significantly, we found a clinically important false-negative rate for the self-measurements. Eleven percent of normal-weight and 52% of overweight women had a professionally measured waist circumference putting them in a high-risk category for metabolic syndrome (ie, greater than 88 cm); however, 57% and 18% of these women, respectively, undermeasured their waist circumference as falling below that cutoff. Fifteen percent and 84% of overweight and class I obese men, respectively, had a professionally measured waist circumference putting them in the high-risk category (ie, greater than 102 cm); however, 23% and 16% of these men, respectively, undermeasured their waist circumference as falling below that cutoff. CONCLUSIONS: Despite standardized pictorial instructions for self-measured waist circumference, the false-negative rate of self-measurements approached or exceeded 20% for some groups at high risk for poor health outcomes.